Memorial EJA e SOME: os impactos na minha vida acadêmica - PINTO, Aldemy Silva (2023)
The present work under the theme EJA AND SOME: The impacts on my academic life brings an approach about my life history as a student, teacher and academic which through my memories I propose possible reflections on the difficulties that accompany the student of this modality of teaching on the agenda and that also hinder their continuation in their studies due to lack of mastery of mathematical knowledge, among others. I also talk about the difficulties I had as a student of EJA and SOME with regard to the knowledge of some subjects, among them Mathematics. This discussion will help us to understand how these teaching modalities often leave much to be desired, as students, both in one modality and in the other, are left without studying certain subjects of paramount importance due to lack of time. This leads us to ask, if in these modalities students finish the courses with many difficulties, now just imagine what happens to those students who study once a week and complete high school in one year. Questions like these will make us reflect on the quality of teaching that some private institutes offer out there and rethink what kind of professionals are being formed. As an EJA teacher, I highlight some positive and negative aspects of this teaching modality and the way it was treated by the school. For the construction of this work, I will use a descriptive autobiographical, reflective and bibliographic research, seeking to establish a possible relationship between my story and the proposed theme, through a qualitative approach, taking into account a dynamic relationship between the subject and the context in which he is. inserted. Using as a textual genre the memorial that has been widely used in academic works, which I will theoretically base through Freire (1987) and (1996), Tardiff (2012) as they discuss about the reflections of this memorial. It is structured in three chapters, in the first I will talk about the beginning of my life story, in the second about my professional preparation and in the third I will talk about my relationship with the university. Finally, I will make the final considerations, in which I will show the results obtained by this research.